Reducing economic imbalances in the euro area: Some remarks on the current stability programs, 2011-14 - Gregor Semieniuk; Till van Treeck; Achim Truger (Levy Economics Institute of Bard College, 2011)
This paper evaluates whether the 2011 national stability programs (SPs) of the euro area countries are instrumental in achieving economic stability in the European Monetary Union (EMU). In particular, we analyze how the SPs address the double challenge of public deficits and external imbalances. Our analysis rests, first, on the accounting identities of the public, private, and foreign financial balances; and second, on the consideration of all SPs at once rather than separately. We find that conclusions are optimistic regarding GDP growth and fiscal consolidation, while current account rebalancing is neglected. The current SPs reach these conclusions by assuming strong global export markets, entrenched current account imbalances within the EMU as well as the deterioration of private financial balances in the current account deficit countries. By means of our simulations we conclude, on the one hand, that the failure of favorable global macroeconomic developments to materialize may lead to the opposite of the desired stability by exacerbating imbalances in the euro area. On the other hand, given symmetric efforts at rebalancing, the simulation suggests that for surplus countries that reduce their current account, a more expansionary fiscal policy will likely be required to maintain growth rates.
Keywords: E10; E17; E62; F42; 330; Euro area; stability programs; current account imbalances; fiscal policy; stability and growth pact